Integration of Artificial Intelligence (AI) in Arabic Language Learning in the Era of Society 5.0 - Aina Syaza Syazwina; Yuyun Zunairoh (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This article examines the integration of Artificial Intelligence (AI) in Arabic language learning in the era of Society 5.0, focusing on pedagogical implications, language competency development, and challenges and directions for development. This study uses a qualitative approach, employing a literature review with a conceptual-critical analysis of reputable journal articles on AI in language education and technology-based Arabic language learning. The results of the study indicate that integrating AI through adaptive learning models, intelligent tutoring systems, conversational chatbots, and voice recognition technology significantly improves students' phonological, lexical, grammatical, and receptive and productive skills. In addition, AI encourages more personalised, interactive, and sustainable learning, while increasing motivation and independence in learning. However, the implementation of AI also presents pedagogical and ethical challenges, such as educator readiness, digital literacy, algorithmic bias, and cultural-religious sensitivity in Arabic. The novelty of this research lies in the formulation of an integrative conceptual framework that positions AI as a humanistic pedagogical medium that is in harmony with linguistic characteristics, cultural values, and the principles of Society 5.0. This study is expected to serve as a theoretical and practical reference for the development of adaptive and ethical AI-based Arabic language learning.